Efektivitas Penggunaan Essential Oil Bunga Melati (Jasminum Grandiflorum) Terhadap Tingkat Kecemasan Pasien Pencabutan Gigi - Muhammad Fajrin Wijaya; Ardian Jayakusuma Amran; Risnayanti Anas; Nur Fadhilah Arifin; Vina Riana Idrus (Inovasi Kesehatan Global, 2025)
Tooth extraction is a minor surgical procedure involving hard and soft tissues in the oral cavity. The level of anxiety towards dental treatment procedures ranks fifth among several other common symptoms that can cause anxiety. Treatment to reduce the level of patient anxiety can be done with pharmacological and non-pharmacological approaches. Jasmine flower essential oil (Jasminun grandiflorum) is one of the non-pharmacological methods used to reduce the level of anxiety in tooth extraction patients. To determine the effectiveness of using jasmine flower essential oil (Jasminum grandiflorum) on the level of anxiety in tooth extraction patients. This study was conducted at the Regional Special Hospital for Teeth and Mouth (RSKDGM) in Makassar. This study is a quasi-experimental study with a pretest-posttest approach. The measuring instrument used was the Modified Dental Anxiety Scale (MDAS) questionnaire which was given before and after giving jasmine flower essential oil for 10 minutes to reduce the level of anxiety in tooth extraction patients. Based on the results of the Wilcoxon test, it showed a significant decrease in the level of anxiety in patients after inhalation of jasmine flower essential oil aromatherapy. Before treatment, the majority of patients had moderate anxiety (47.9%), while after treatment, mild anxiety increased to 89.6% (p-value 0.000). Jasmine Flower (Jasminun Grandiflorum) essential oil is effective in reducing the level of anxiety in tooth extraction patients.